1979
DOI: 10.1056/nejm197903223001202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Control of Blood Glucose on Urinary Excretion of Albumin and β2Microglobulin in Insulin-Dependent Diabetes

Abstract: To study the effects of improved control of blood glucose on markers of renal glomerular and tubular function, we initially determined, by radioimmunoassay technics, urinary excretion rates of albumin and beta2 microglobulin in 17 nondiabetic subjects and in 43 insulin-dependent, clinically nonproteinuric diabetic patients. Duration of diabetes ranged from six months to 39 years, and the patients were studied while receiving conventional therapy. Mean urinary albumin excretion was significantly elevated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
1
1

Year Published

1983
1983
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(85 citation statements)
references
References 10 publications
5
75
1
1
Order By: Relevance
“…An abnormal value could be a transient phenomenon due to a number of factors, even perhaps changes in glucose levels (17). Our data could be consistent with this concept because there was a marked association between albumin excretion and fasting glucose levels.…”
Section: Sosenko Kato and Goldbergsupporting
confidence: 84%
“…An abnormal value could be a transient phenomenon due to a number of factors, even perhaps changes in glucose levels (17). Our data could be consistent with this concept because there was a marked association between albumin excretion and fasting glucose levels.…”
Section: Sosenko Kato and Goldbergsupporting
confidence: 84%
“…In contrast, measures of the extent of mesangial expansion and peripheral capillary surface were related to levels of albuminuria that would be clinically detectable by Albustix. It is known that the microalbuminuria of diabetic patients without clinical nephropathy (4,5) is reversible by the institution of short-term strict glycemic control (5), whereas in diabetic patients with overt proteinuria, fractional IgG and albumin clearances continue to increase and GFR continues to decrease despite 6 mo of strict glycemic control (41). It is also known that the onset of overt proteinuria ushers in the development of a progressive deterioration in the macromolecular permselective characteristics of the glomerular barrier (38,42).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence both for and against comes largely from populations of Type II diabetics. Viberti et al (1979Viberti et al ( , 1981 showed that near-normoglycaemia produced by continuous subcutaneous insulin infusion in Type I diabetics rapidly reduced elevated levels of albumin uria measured by the sensitive radioimmunoassay.…”
Section: Factors Affecting Rate Of Progression Of Nephropathymentioning
confidence: 99%